Women and the abuse of power : interdisciplinary perspectives - Gavin, Helen (Emerald Interdisciplinary Connexions Ser., 2022)
With themes ranging from the personal consideration of female bodies, to the supernatural hidden realm, to the public condemnation of women who fall foul of either the law or of a male-dominated world, this collection of interdisciplinary essays provides an in-depth look at the fate of women who abuse or are abused by power.